Layered Bimetallic Metal‐Organic Material Derived Cu2SnS3/SnS2/C Composite for Anode Applications in Lithium‐Ion Batteries. Issue 23 (25th September 2018) - Foley, Sarah; Geaney, Hugh; Bree, Gerard; Mukherjee, Soumya; Zaworotko, Michael J.; Ryan, Kevin M.
Abstract: Here, we report the synthesis of a bimetallic 2D interpenetrated metal‐organic material (MOM) and its use as a sacrificial precursor for the formation of a Cu2 SnS3 /SnS2 /C composite. The one‐step sulfurisation of the novel Sn/Cu‐MOM represents a facile method for the preparation of an effective anode material for Li‐ion battery applications. The Cu2 SnS3 /SnS2 /C composite was characterised by XRD, TGA, TEM and SEM. Electrochemical analysis was conducted on SnCu2 SnS3 /SnS2 /C anodes in half cell configurations between 0–3 V and 0–1 V. Anodes cycled between 0–1 V exhibited markedly more stable capacity retention (315 mAh/g after 100 cycles), as only alloying of the Li with Sn took place within this potential window, compared to a combination of conversion and alloying for the wider potential range. This stability of the Li alloying based capacity was further enhanced by replacing the planar Cu foil with a rough dendritic Cu foil as the current collector, resulting in an improved capacity retention of 84 % after 100 cycles. Abstract : Boost from precursor chemistry : a bimetallic 2D interpenetrated metal‐organic material is used as sacrificial precursor for the formation of a Cu2 SnS3 /SnS2 /C composite as anode for Li‐ion batteries. The anodes are cycled in potential ranges between 0–3 V and 0–1 V in half cell configuration. In the wider potential range, conversion and alloying of Li with Sn takes place while in the smaller potential window only alloying is observed, leading to a more stable capacity retention.